Food insecurity among university students at two selected public universities in Malaysia - Ramlee, Izwan Syafiq; Ali, Asma’; Zalbahar, Nurzalinda; Abdul Wahab, Rahijan; Jaafar, Siti Nur ‘Afifah (Malaysian Society of Applied Biology, 2019)
Most of food insecurity studies focus on the general households’ level and less have been done for the university students. Therefore, this cross-sectional study focused on determining food insecurity, assessing factors contributing to the food insecurity and the association between socioeconomic status and food security status among students in two public universities in Terengganu. About 96 undergraduate students from two selected public universities in Terengganu participated and filled out a self-administered questionnaire consisting of three primary sections; Demographic profile, Food Security Index and Causes of Food Insecure and these were later analysed by SPSS. Results showed that 22% of respondents were classified as food insecure, with 14% of them were categorized in the low food security group and 8% were categorized as very low food security. High cost of living is among the main factors contributing to food insecurity among the university students in Terengganu. However, no significant association was found between socio-economic status and food insecurity status at p<0.05. This may indicate that there are other factors besides socioeconomic status, which may influence food insecurity of the students in this study. In the future, similar studies should be extended to focus on assessing students’ food insecurity and food coping strategies.